Hubungan Pola Menstruasi Dengan Kejadian Anemia Pada Remaja Putri Di SMPN 6 Tapung Kabupaten Kampar - Sriwidya Astuti Khati (Pusat Riset dan Inovasi Nasional, 2024)
Anaemia is a public health problem that occurs throughout the world, especially in developing countries such as Indonesia, the prevalence of anaemia in women of reproductive age between the ages of (15-49) in the world in 2019 ranged as much as 29.9%. This study aims to determine the relationship between menstrual pattern variables and the incidence of anaemia. The design of this study was cross sectional. The sample in this study was 100 respondents. The hypothesis test used was the Chi-square test. The results of this study are that there is a significant relationship between menstrual patterns and the incidence of anaemia in adolescent girls at SMPN 6 Tapung Kampar Regency in 2023, the value of P value = 0.002 OR (95% CI: 1.778-9.87), and there is a significant relationship between menstrual patterns and the incidence of anaemia in adolescent girls at SMPN 6 Tapung Kampar Regency. It is expected for health workers to be able to make creative and innovative policies in the prevention of anaemia through increasing health education and promotion in schools and fostering the PIK-KRR program (Adolescent Reproductive Health Information and Counseling Center) and UKS (School Health Unit), as well as facilitating adolescents to participate.